Plano de gerenciamento de resíduos sólidos em instituições públicas de ensino superior: uma análise documental e identificação de melhores práticas - Silveira, Bianca Cristina Francischinelli da (Universidade Federal de São Carlos, 2024)
Public higher education institutions in Brazil are legally obligated to develop Solid Waste Management Plans (PGRS), emphasizing environmental responsibility and sustainable waste management. Thus, this study was conducted through documentary analysis of the PGRS at the Federal University of Santa Maria (UFSM) and the Federal University of Pernambuco (UFPE), following the guidelines of the National Solid Waste Plan (PNRS) and other applicable regulations. Both institutions were selected, and the analysis was carried out based on items established in a checklist, in addition to using the SWOT matrix. The analysis of both plans revealed gaps, particularly concerning environmental liabilities, shared responsibility actions, and the scope of waste types on campuses. It was observed that few Brazilian public universities have an identifiable online PGRS. In this context, collaboration between universities and government bodies becomes crucial to align policies with the institutions' needs and capacities, promoting an integrated and sustainable approach to solid waste management. For future research, it is suggested to analyze the implementation of PGRS in international universities and different types of educational institutions, seeking a better understanding of their effectiveness in waste management and handling.
Solid waste management plan in public higher education institutions: a documentary analysis and identification of best practices
Keywords: Instituições públicas de ensino superior; Gestão de resíduos; Plano de gerenciamento de resíduos sólidos; Análise SWOT; Higher education institutions; Waste management; Solid waste management plan; SWOT Analysis; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS